Antibacterian in vitro determinatíon of Menthostachys mollis (Muña) opposite to oral bacterial stomatological importance - Díaz L., Karin (2005)
With the aim to determine the antimícrobial action of the essential oil of Methosthachys mollis (Muña); in design at random one strains standard ATCC of Streptococcus mutans, Lactobacillus sp, Fusobacterium nucleatum, Actinobacillus actinomicetencomitans and Actinomyces sp, to: Amoxicilina (positive witness), essential oil of Methosthachys mollis and, distilled water (negative witness); to measure the halos of antitmicrobial action. For the mentioned bacteria one found, respectively, in Amoxicilina the following diameters averages in mm: 68; 42,75; 50,5; 51,58 and 33,25; in Methosthachys mollis: 16,50; 14,38; 20,13; 18,43 and 11. These results are statistically different. Halo of antimicrobial action was not observed in the negative witness. One concludes that Methosthachys mollis has antimicrobial effects on the most important oral bacteria, with an average of 16,75 mm of diameter of the halo.